CENTRAL ACEH GOVERNMENT’S ROLE POST THE ENACTION OF GAYO COFFEE’S GEOGRAPHICAL INDICATIONS - Novi Syafriani; M. Putra Iqbal (Fakultas Hukum Universitas Syiah Kuala, 2018)
Indonesia as a member of the World Trade Organization (WTO) has a duty to implement the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPs). TRIPs Agreement is the international regulatory framework on protection of intellectual property. According to TRIPs Agreement, Geographical Indication is an intellectual property right conferred to protect the name of a specific place (region, locality or even country) where a product originates, as well as the special qualities, characteristics and reputation, due to natural factors and/or to traditional productions practices that are directly linked to such origin. One of Indonesian products that has received a Geograpical Indication status is Kopi Gayo coffee. Kopi Gayo coffee has been registered in the General Directorate of IPR Indonesia and also had been registered in European Union (EU). The focus of this thesis is to explore how are the efforts of local governments to maintain the Geographical Indications on Kopi Gayo coffee and to comprehend the obstacles in the implementation of registered Geographical Indications on Gayo Coffee. This research uses empirical method. The data in this paper was obtained by studying related fields of study, interviewing on respondents and informants, and conducting library research to acquire secondary data which sources include; legislations, books, online documents and other scholarly works related to research problems. Article 4 of Government Regulation No. 51 Year 2007 stipulates that registered Geographical Indication shall be protected as far as the specific characteristics and quality which have been the basis of the protection grant still exist. Therefore, the roles of government, farmers and exporters need to be fulfilled in order to maintain Geographical Indication on Kopi Gayo Coffee. Government created Masyarakat Perlindungan Kopi Gayo (MPKG) as a public institution for registering geographical indication and then becomes the milestone of society and government to preserve the existence of Kopi Gayo coffee. Moreover, government should aware of the legal protection Kopi Gayo for its sustainance. Until now, Kopi Gayo has managed to penetrate the international market but still need improvement on the quality of its local human resources. Monitoring and surveillance are being conducted by the Government to maintain the characteristics of Kopi Gayo. In spite of many government-arranged programs, there are various aspects that the government has not yet to consider. Currently, the effort that has been made by government is insufficient to protect Gayo coffee. The government admitted to have a shortage of financial and human resource that are capable to provide guidance regarding geographical indication. Therefore, it is recommended that the government optimize legal protection of geographical indication and learn from other regions which have the geographical indication product to preserve the existence of Kopi Gayo coffee.